The copper bearing traps of the Coppermine River [electronic resource] - Douglas, James, 1837-1918. ([Ottawa? : s.n., 1913)
Caption title. "(Annual meeting, Ottawa, 1913)" Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44